2011
DOI: 10.1007/s11739-011-0609-4
|View full text |Cite
|
Sign up to set email alerts
|

Is nonalcoholic steatohepatitis associated with a high-though-normal thyroid stimulating hormone level and lower cholesterol levels?

Abstract: Hypothyroidism is associated with the risk of development of the metabolic syndrome (MS) and hypercholesterolemia. Direct evidence that hypothyroidism might be associated with advanced chronic liver disease via nonalcoholic steatohepatitis (NASH) is limited. We studied the relationship between thyroid hormones, thyroid stimulating hormone (TSH), cholesterol, and NASH. In consecutive euthyroid patients with biopsy-proven nonalcoholic fatty liver disease, TSH and thyroid hormone (FT3 and FT4) concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 40 publications
5
65
0
2
Order By: Relevance
“…Beside the inverse association with FT4, Chung et al and Xu et al identified a positive association between NAFLD and TSH. This association was observed in other studies (32,35).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Beside the inverse association with FT4, Chung et al and Xu et al identified a positive association between NAFLD and TSH. This association was observed in other studies (32,35).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have investigated the association between NAFLD and thyroid function in adult or elderly patients (29,30,32,33 ). The study by Targher et al involving a large cohort of unselected adult outpatients was the first to report a strong association between thyroid function tests and serum liver enzyme activity concentrations (33).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypothyroidism among a cohort of 246 patients with biopsy-proven NAFLD was 21 vs 9.5% in 430 age-, gender-, race-and BMI-matched controls (90). In addition, the prevalence of hypothyroidism in patients with NASH is higher than those with more benign disease (90,91). There are currently no published studies that have examined NAFLD in the context of hyperthyroidism.…”
Section: Thyroidmentioning
confidence: 99%
“…Hypothyroidism is associated with a risk of developing metabolic syndrome, and several groups have shown the relationship between hypothyroidism and NAFLD and hypothyroidism and NASH (6)(7)(8)(9)(10). However, the relationships between hypothyroidism and NAFLD and hypothyroidism and NASH remain controversial.…”
Section: Introductionmentioning
confidence: 99%